The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/0104-6632.20150322s00003066
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Copolymeric and Terpolymeric Hydrogel-Silver Nanocomposites Based on Acrylic Acid, Acrylamide and Itaconic Acid: Investigation of Their Antibacterial Activity Against Gram-Negative Bacteria

Abstract: -In this study, copolymeric and terpolymeric hydrogel-silver nanocomposites based on poly(acrylamideco-itaconic acid), poly(acrylic acid-co-itaconic acid) and poly(acrylic acid-co-acrylamide-co-itaconic acid) were synthesized by free-radical polymerization. These nanocomposites were characterized by Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), UV-Visible Spectrophotometry (UVVis) and X-Ray Diffraction (XRD) analysis, as well as their swelling behaviors. In addition, antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 40 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…Among those are biocompatible and often biodegradable polymers such as alginate, chitosan (CHI), poly(vinyl alcohol) (PVA), poly(vinyl pyrrolidone) (PVP), cellulose, etc. [3][4][5][6][7][8][9][10][11]. Of course, apart from biocompatibility, hydrogel-based wound dressings must satisfy several other stringent requirements, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Among those are biocompatible and often biodegradable polymers such as alginate, chitosan (CHI), poly(vinyl alcohol) (PVA), poly(vinyl pyrrolidone) (PVP), cellulose, etc. [3][4][5][6][7][8][9][10][11]. Of course, apart from biocompatibility, hydrogel-based wound dressings must satisfy several other stringent requirements, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thomas et al [11] have been reported nano particles such as silver, gold, and copper is highly toxic to microorganisms due to their strong biocidal effects. Bal1 et al [12] have prepared itaconic acid based silver nanocomposite hydrogels with a lesser swelling ratio due to Ag + complexation with carboxyl moieties. Tibbitt et al [13], reported that for stem cell engineering, immunomodulation and cancer research applications demand multiple functionalities of the hydrogel network and dynamic interactions between the surrounding cells.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of nanoparticles has allowed the scientific community to enhance the antibacterial properties of silver. The increased surface area of the nanoparticles in turn induces an increased rate of interaction between the test subjects and the ionic silver (Alexander, 2009;Nam et al, 2015;Bal et al, 2015;Dong et al, 2016;Mckevica et al, 2016;Amadio et al, 2017).…”
Section: Introductionmentioning
confidence: 99%